When is self-labeling seen as reclaiming? The role of user and observer's sexual orientation in processing homophobic and category labels’ use - Sturaro, S.; Suitner, C.; Fasoli, F. (Journal of Language and Social Psychology, 2023)
Reclaiming involves self-labeling with derogatory labels. This behavior can be processed differently depending on contextual factors: Type of label, user, and observer. Sexual minority and heterosexual participants saw a vignette depicting either a gay or a heterosexual man who self-labeled with a derogatory or a category label. Sexual minority participants perceived the act of self-labeling with a derogatory label by a gay man as less offensive than heterosexual participants did. Sexual minorities, more than heterosexual participants, perceived self-labeling as powerful.